Peluang Riset tentang Peran Karakteristik Informasi Sistem Akuntansi Manajemen (SAM) di Perusahaan Jasa - Rahman, Aulia Fuad (TEMA, 2006)
The objectives of this paper are to briefly review literature on management accounting system (MAS) information characteristics in manufacturing companies and to propose research opportunity related to the role of MAS information characteristics in service companies. Two steps are involved in developing research propositions. First, identifying contingent characteristics facing professional and mass service type. Second, matching the contingent characteristics for each type of service company with the appropriate MAS information characteristics based on the prior results of research in manufacturing companies. Contingent characteristics of professional service can be identified as high environmental uncertainty, high task uncertainty and decentralized organizational structure. On the other hand, contingent characteristics of mass service are low environmental uncertainty, low task uncertainty and centralized organizational structure. Based on the contingent characteristics identified for professional and mass service type, six propositions are proposed as the opportunities for future research on the role of MAS information characteristics in service companies. Key words: MAS information characteristics, service organization